Editorial: Pathogen suppression by plant-associated microbiota - Herrera-Vásquez, Ariel; Schlechter, Rudolf; Armijo-Godoy, Grace; Monteoliva, Mariela Ines (Frontiers Media, 2025)
Plants interact with a broad spectrum of microorganisms, including non-pathogenic microbes, which play a crucial role in plant health, productivity, and stress resilience. While pathogens have been widely studied due to their detrimental impact on crops, research on beneficial microorganisms is increasing exponentially. Among them, the most extensively explored symbiotic interactions include nitrogen-fixing bacteria, mycorrhizal associations, and microbiota-driven pathogen suppression (Tharanath et al., 2024).